'Suddenly the bone snapped in two': Freud, fantasy, and Taran Wanderer. Issue 1 (3rd July 2021) - Butchart, Liam
ABSTRACT: Lloyd Alexander's Chronicles of Prydain have garnered both critical interest and popular acclaim. Notably, the fourth book of the cycle, Taran Wanderer, is strikingly different from its predecessors, shedding much of the trappings of high fantasy for a simple bildungsroman . This paper examines the text, using Freud's theories of symbolism, the family romance and the Oedipal conflict, to elucidate Taran's underlying psychology and to show how the character's unconscious motivations, molded by his identity as a foundling, drive the narrative. Finally, by applying insights gained from reader-response theory, this paper considers why Taran Wanderer, and adolescent fantasy literature more broadly, resonates so strongly with readers.